Development of a Biomass Supply Chain Model for Renewable Energy: Preparing for the Green Economy - Aang Gunawan; Abdullah Ade Suryobuwono; Sita Aniisah Sholihah (Dinasti International Journal of Education Management and Social Science, 2025)
Indonesia faces a significant gap in achieving its New and Renewable Energy (NRE) mix target of 23% by 2025. The biomass co-firing program in existing coal-fired power plants (CFPPs) has emerged as a flagship strategy for PT PLN (Persero) to accelerate this transition. However, the program's success is jeopardized by fundamental challenges within the biomass supply chain. The current supply chain is characterized by a fragmented, point-to-point model that has proven inefficient and gives rise to systemic issues, including high logistics costs, supply uncertainty, and a failure of upstream quality control, exemplified by sawdust moisture content frequently exceeding 45%. This research aims to (1) empirically analyze the weaknesses of the existing supply chain at four major CFPPs in Java, (2) design an optimized supply chain framework using a hub-and-spoke model, and (3) develop a techno-economic model for standardizing transportation tariffs. The research methodology integrates field surveys with quantitative modeling, employing a Vehicle Operating Cost (VOC) approach based on Minister of Transportation Regulation No. 60 of 2019 as the foundation for a cost simulator. The analysis confirms that the current point-to-point model is uneconomical due to extreme travel distances (up to 380 km), low asset utilization (50% load factor), and misaligned incentive structures. The proposed hub-and-spoke model is designed for hubs to function as centers for aggregation, pre-processing (drying, densification), quality control (in accordance with SNI 8675:2018), and buffer stocking. The VOC simulation validates the economic feasibility of this model, demonstrating significant cost savings through economies of scale (use of large-capacity trucks) and route optimization. This study concludes that the adoption of a hub-and-spoke model is a strategic prerequisite for the sustainability of the co-firing program. Policy recommendations include the implementation of a pilot project, the restructuring of procurement contracts based on the VOC model, and government incentives for hub development.